The Resilience of Syrian Refugee Children in Lebanon : What Do They Need to Acquire Quality Education? - Abu-Amsha, Oula (World Bank, Washington, DC, 2015)
Since the beginning of the turmoil in Syria, more than one million Syrians have been forced to leave their country and find refuge in Lebanon, a small neighboring country with limited resources and its own political, social and economic challenges. This report presents the findings of a pilot study that follows the Education Resilience Approaches (ERA) framework (Reyes 2013). The purpose of the research is to discover the different risks, assets, and processes that influence the learning achievement of Syrian refugee children trying to access education services in Lebanon. The difficulties that confront Syrian children in the Lebanese education system are not simply due to the difference in languages of instruction as it seems to be at a first glance. This study reveals how many children could overcome the language barrier through traditional and simple means such as extracurricular language instruction and proper support. The study also reveals that the feelings of discrimination and exclusion felt by Lebanese peers are often the result of individual and communal apprehension and not necessarily the result of real incident (except minor ones).